If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8 + 2x + -7 = 15 Reorder the terms: -8 + -7 + 2x + 2x = 15 Combine like terms: -8 + -7 = -15 -15 + 2x + 2x = 15 Combine like terms: 2x + 2x = 4x -15 + 4x = 15 Solving -15 + 4x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 4x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + 4x = 15 + 15 4x = 15 + 15 Combine like terms: 15 + 15 = 30 4x = 30 Divide each side by '4'. x = 7.5 Simplifying x = 7.5
| -0.6+(-0.3)= | | -4+(v-2)=-4(v-8)-8v | | 3x-5x+7=-21 | | 4(x-3)-1=3x | | 4n+2=6n+8 | | 7=-11+3(y+5) | | 3y=-5x+6 | | m^2+mn-6n^2=0 | | 3x+4xy-(4x-xy+xyz)= | | 19=-2p+23 | | 0=14x+28 | | 6(4-w)=2w | | 5x-3=3(x+6) | | 3/2=18÷x | | 6a-5b=1 | | X^2+3x-12+-6=0 | | 3x+4-9-4x=12 | | v=4/3*3.14*(21)3 | | 4x=2(48-4) | | h/6-1= | | x(4x-6)=(4x+7)(x-5) | | 5X1/14 | | 2x+x-24=90 | | X-1=4x-22 | | 4x=2(48-3) | | 15x-3x+2(x+4)=48 | | z^2+3z=-1 | | 13-4t+5t=-5-2 | | 11/4y-3/12y=10 | | (13+a)+14= | | 7x+3x-2=-3(-11-x) | | 3k+6=9 |